Святий-“єретик” Григорій Палама про внутрішнє буття пресвятої трійці - Zhukovskyy, Viktor (Vox Patrum, 2018)
The article examines the figure and the teaching of the famous Byzantine theologian, Hesychast and Church leader of the fourteenth century St. Gregory Palamas. The author considers the problem of the intratrinitarian being of God in the Palamas’ doctrine and analyses the key characteristics of this “hidden” dimension of the Holy Trinity. Special attention is paid to the analysis of the apophatic approaches in answering the question: how can God, who is actively present in the created world and filling it, be at the same time completely ontologically removed from created reality. In this context the author analyses the key notions which express the “intradivine” transcendence of God’s being: ousia, hipostasis, intratrinitarian relation, theologia, oikonomia.